Investigation on Performance of PDMS-Graphene/PES Hybrid Membrane for Pervaporative Separation of Phenol from Aqueous Streams. Issue 3 (11th February 2019) - Rahmani, Saqar; Mortaheb, Hamid Reza; Omidkhah, Mohammad Reza; Khodadadi Dizaji, Azam
ABSTRACT: The pervaporative performances of pristine polydimethylsiloxane (PDMS) membrane and modified one by hybridizing with graphene nanosheets (PDMS-G) were evaluated for phenol removal from aqueous solutions. The incorporation of hydrophobic graphene nanosheets could enhance the process performance. The optimum performance was determined at 0.2 wt% crosslinker concentration and 0.2 wt% graphene content with a significant improvement in the separation factor up to 42.35. The enhanced separation factor can be attributed to optimized interfacial free volume in the structure of the membranes and formation of π-π interactions between graphene and phenol. The effects of operating parameters on separation performance were also evaluated. GRAPHICAL ABSTRACT: